The Importance of Integrating ICT Into Islamic Study Teaching and Learning Process - Engkizar, Engkizar; Muliati, Indah; Rahman, Rini; Alfurqan, Alfurqan (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2017)
Teachers of Islamic Study bear a great responsibility to help students have a balanced personality; physics, emotions, and intelligence consistent with the philosophy of Islamic Study and the goal of national Education. The courses of Islamic Study, aqidah, observance, akhlak, fiqih, alquran and history require various strategies, methods, and teaching media. It is considered inappropriate if teachers of Islamic Study spend most of the hours explaining all materials about shalat, hajj, and the history of Islam using ‘chalk and talk’ strategy. Therefore, applying ICT in the classroom such as using computers and internet connection in a teaching and learning process is likely to be an alternative. Some other previous research showed that many Islamic Study teachers were seldom applying ICT during the teaching and learning process. It might be due to the lack of facilities and training, and teachers’ low esteem. This article explains how integrated ICT; computers and internet connections may support the teaching and learning process in the classroom. The explanation is strengthened by some theories, experts’ reviews and previous research findings related to the Islamic Study. The findings of the article are expected to provide references that may be used to integrate ICT in the teaching and learning process.